2022
DOI: 10.1371/journal.pone.0263378
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of cardiac magnetic resonance in patients with aortic stenosis: A systematic review and meta-analysis

Abstract: Background The timing of surgery for aortic stenosis (AS) is imperfect, and the management of moderate AS and asymptomatic severe AS is still challenging. Myocardial fibrosis (MF) is the main pathological basis of cardiac decompensation in patients with AS and can be detected by cardiovascular magnetic resonance (CMR). The aim of this study was to evaluate the prognostic value of MF measured by CMR in patients with AS, which can provide a reference for the timing of aortic valve replacement (AVR). Methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In addition, we did not examine changes in cardiac structure following TAVI. While evidence suggests that persistent fibrosis following TAVI may be central to future HF, 49 further studies in this cohort and others are required to understand how baseline pre‐TAVI metabolism and changes following TAVI correspond to the capacity for reverse remodeling in the heart (and other organs). The cohorts studied underwent TAVI ≥5 years ago, which may limit generalizability to contemporary cohorts.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, we did not examine changes in cardiac structure following TAVI. While evidence suggests that persistent fibrosis following TAVI may be central to future HF, 49 further studies in this cohort and others are required to understand how baseline pre‐TAVI metabolism and changes following TAVI correspond to the capacity for reverse remodeling in the heart (and other organs). The cohorts studied underwent TAVI ≥5 years ago, which may limit generalizability to contemporary cohorts.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, CMR's ability to detect myocardial fibrosis contributes to prognostic value in AS patients, optimizing the timing of AVR for improved outcomes. 84 …”
Section: Diagnosis Of Amyloidosis In the Setting Of Aortic Stenosismentioning
confidence: 99%
“…Regarding AS, CMR can be used to assess myocardial fibrosis and to identify risk factors 98,99. A recent meta-analysis100 demonstrated that CMR helps in risk stratification of AS and may help optimize the timing of aortic valve replacement. The assessment of the aortic valve and aortic root in CMR is helpful in TAVR procedures, especially in patients who cannot be assessed by CT imaging 101…”
Section: Imaging In Structural Heart Diseasementioning
confidence: 99%